Fatty acid profile of jelawat fish (Leptobarbus hoevennii) based on different harvesting time - Dewi Kusuma Anggraini; Edison '; Sumarto ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This research aimed to determine the chemical compositions and fatty acid profile of jelawat fish based on harvesting time. The research was conducted on September until October 2014. This research used the experiment method. Harvesting times of this research were 6, 10, and 14 months. Proximate analysis of three samples were tested by the thermogravimetric method, soxhlet method and kjeldahl method (AOAC 1995). Analysis of fatty acid used Gas Cromatography method (AACC 1983). The average value of proximate jelawat fish for harvesting time 6, 10, dan 14 months a row are moisture content 68.93%, 66.81%, 66.23%, ash 1.52%, 1.23%, 1.14%, protein content 23.03%, 23.56%, 20.91%, and fat content 6.12%, 8.31%, 10.73%. Based on the analysis, there are 26 kinds of fatty acids identified in fat jelawat fish. The fatty acids consist of 10 kinds of saturated fatty acids and 16 kinds of unsaturated fatty acids. The results showed that jelawat fish for harvesting time 6 to 10 months have a fatty acid content optimally with each total unsaturated fatty acids 52.76% and 51.84%.Keywords: fatty acid, harvesting time, jelawat fish